Avaliação da fragilidade ambiental em bacias hidrográficas do alto vale do rio Pirapá, Norte do Paraná : proposta metodológica - Bonifácio, Cássia Maria (2013)
The aim of this research was the development and application of a methodology for the environmental fragility evaluation in upper Pirapó river watersheds basins: the basin of Alegre creek and the basin of the Sória creek, the first one is representative of the left bank, and the second one the right bank in the sector of the analyzed basin. Based on existing methodologies, we tried to develop a form of evaluation that would enable the development of synthetic charts of environmental fragility, which would reflect the essential geoecological structure of the landscape and also at the same time easier to understand. The methodological approach came from the integrated analysis of the landscape aimed to survey its geoecological structure, the operation and identification of the several landscapes units presented in the inner area of the selected basins, whilst the environmental fragility cartography relied in the identification and the morphopedological characteristics reflection along the slopes. In this methodological approach the defining element of the class of the potential fragility was the type of soil and the slope that became the element that ranks the degree of fragility within each class. The forms of land use have been incorporated, as has been customary, as elements of transformation and triggering new dynamics, generating the emergent fragility chart. The results showed that significant differences occur between the basins of the tributaries of the right bank and those of the left bank in the considered sector. The observations and the integrated analysis of the elements that compose the landscape highlighted the differences and peculiarities between the basins analyzed. In each one of them we found a compartmentalisation that allowed the identification of different landscape units, characterized by distinct geoecological structure that translates also in different strengths and fragilities. The proposed methodology for the classification of fragility, in turn, was able to reproduce the observed differences in the geoecological structure and the associated dynamics (processes), recommending it as a tool to be applied to environmental zoning.